2021
DOI: 10.1039/d1tb00717c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering next-generation bioinks with nanoparticles: moving from reinforcement fillers to multifunctional nanoelements

Abstract: The application of additive manufacturing in the biomedical field has become a hot topic in the last decade owing to its potential to provide personalized solutions for patients. Different bioinks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 135 publications
(148 reference statements)
0
30
0
1
Order By: Relevance
“…Several studies have shown that bioink printability is governed by bioink composition and printing parameters. , To enhance the printability and shear-thinning properties of hydrogels in general, incorporation of different additives such as nanoparticles and 2D materials has been employed and has, so far, demonstrated excellent results. For GelMA hydrogels, in particular, efforts have been devoted to high concentrations rather than low ones, although low concentrations produce better cell-laden constructs …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that bioink printability is governed by bioink composition and printing parameters. , To enhance the printability and shear-thinning properties of hydrogels in general, incorporation of different additives such as nanoparticles and 2D materials has been employed and has, so far, demonstrated excellent results. For GelMA hydrogels, in particular, efforts have been devoted to high concentrations rather than low ones, although low concentrations produce better cell-laden constructs …”
Section: Introductionmentioning
confidence: 99%
“…For example, biofabrication is an emerging and rapidly growing research field in which additive manufacturing has been merged with tissue engineering to generate hierarchical tissue-like and personalized constructs. On the basis of 3D bioprinting technology, bioinks combining high-resolution printability with cytocompatibility have been developed as one ideal scaffold material for clinical translation, which will continue to be an active participant in the process of bone regeneration, not only as cells and molecular carriers, but also playing an important role in controlling delivery efficiency and delivery rate, thus making bioprinting hydrogel systems appealing alternatives for tissue engineering and drug delivery purposes, among others [ 93 , 94 , 95 , 96 ]. Therefore, it is of great significance to construct osteoblast and osteoclast co-culture models based on 3D printing techniques for promoting bone regeneration and studying the interaction between cells.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules enhance a more biomimetic microenvironment that simulates the natural signaling and repair mechanisms thus influencing tissue formation and cellular functions (45). Bioactive inorganic fillers and nanomaterials such as graphene, graphene oxide, carbon nanotubes, calcium phosphates, bioactive glasses, silica nanoparticles, and nanoclays have also been used in hydrogel bioinks to improve printability, cell viability, and mechanical properties (155)(156)(157). These fillers could also be doped with drugs or biologically active ions to induce specific responses or act as crosslinkers (155).…”
Section: Scaffoldsmentioning
confidence: 99%
“…These fillers could also be doped with drugs or biologically active ions to induce specific responses or act as crosslinkers (155). We refer the reader to these comprehensive reviews on the topic (155)(156)(157)(158). As an example of functionalization, Modaresifara et al developed a gelatin methacryloyl (GelMA) hydrogel that incorporated chitosan nanoparticles to promote growth factor delivery (158).…”
Section: Scaffoldsmentioning
confidence: 99%